2019
DOI: 10.1007/s10546-018-0420-0
|View full text |Cite
|
Sign up to set email alerts
|

The Onset of Resolved Boundary-Layer Turbulence at Grey-Zone Resolutions

Abstract: Numerical weather prediction (NWP) models are now capable of operating at horizontal resolutions in the 100-m to 1-km range, a grid spacing similar in scale to that of the turbulent eddies present in the atmospheric convective boundary layer (CBL). Known as the 'grey zone' of turbulence, this regime is characterized by significant contributions from both the resolved and subgrid components to represent the dominant motions of the system. This study examines how the initiation of resolved turbulence-a concept c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In Kealy et al (), we found that the manner of imposing the potential temperature perturbations makes a large impact on the CBL evolution in the grey zone. Wondering if a similar effect would appear in a real case, we ran the UM at both 1.5km (the vicinity of the turbulence mesoscale limit) and 400m (deep in the turbulence grey zone), both with the perturbations applied and without them.…”
Section: What About Moist Convection?mentioning
confidence: 52%
See 2 more Smart Citations
“…In Kealy et al (), we found that the manner of imposing the potential temperature perturbations makes a large impact on the CBL evolution in the grey zone. Wondering if a similar effect would appear in a real case, we ran the UM at both 1.5km (the vicinity of the turbulence mesoscale limit) and 400m (deep in the turbulence grey zone), both with the perturbations applied and without them.…”
Section: What About Moist Convection?mentioning
confidence: 52%
“…Similar to Figure , but showing the Kealy et al () method of accelerating spin‐up. The ‘CsCoMLS’ simulation features the addition of structured perturbations to the potential temperature, along with assigning a dependence on boundary‐layer depth to the diffusivity.…”
Section: Perturb Blend and Adjustmentioning
confidence: 89%
See 1 more Smart Citation
“…Incorrectly representing them in a model could, for example, result in systematic errors in wind speed or cloud cover, amongst other things. Careful perturbations of turbulence need to be introduced into the model to allow proper treatment of turbulence (Kealy, Efstathiou, & Beare, 2019). Radar data can be used to derive turbulence statistics for evaluating better parameterization of turbulence in NWP models (Feist et al, 2019).…”
Section: Advances In Physical Modelingmentioning
confidence: 99%
“…Modeling SGS turbulence in the gray zone without missing or double counting turbulent energy is a relatively recent topic of research that still lacks robust and validated solutions [9][10][11][12][13]. For grid spacings larger than the gray-zone upper limit, traditional mesoscale modeling approaches can be used to model the impacts of SGS turbulence on the resolved fields.…”
Section: Introductionmentioning
confidence: 99%